Biophysical and molecular docking insight into interaction mechanism and thermal stability of human serum albumin isoforms with a semi-synthetic water-soluble camptothecin analog irinotecan hydrochloride. Issue 7 (2nd July 2016) - Ishtikhar, Mohd.; Khan, Mohsin Vahid; Khan, Shawez; Chaturvedi, Sumit Kumar; Badr, Gamal; Mahmoud, Mohamed H.; Khan, Rizwan Hasan
Abstract : In the present work, we have examined the binding parameters, thermodynamics, and stability of human serum albumin (HSA) isoforms at pH 7.4 and 9.0, using spectroscopic, calorimetric, and molecular docking methods in the presence of water-soluble camptothecin analog irinotecan hydrochloride (CPT-11). We observed that CPT-11 binds to HSA through a static quenching procedure of ground-state complex formation with N-isoform and B-isoform. Hydrogen bond and hydrophobic interactions are the major governing forces that participating in the formation of protein–drug complex. To determine the binding site of CPT-11 within HSA molecules, we also have performed molecular docking experiments. We explored the CPT-11-mediated stability and modulation of HSA by performing dynamic light scattering (DLS) and differential scanning calorimetry (DSC) experiments. DLS and DSC techniques are used to determine the size and the melting point ( T m ) of HSA, which was decreased in the presence of CPT-11. Therefore, CPT-11 plays an important role in HSA stability and protein–ligand interactions. The present study provides valuable information in the field of pharmacokinetics, pharmaco-dynamics, and drug discovery. Graphical abstract: Irinotecan hydrochloride (CPT-11) binds to HSA through a static quenching mechanism by ground-state complex formation. Hydrophobic interactions and hydrogen bonds played a major role in protein–drug complex formation. The melting point ( T m ) of HSA was decreased in the presence of CPT-11 as compared to native HSA that was determined by DSC for both isoforms of HSA.